Influence of injection well configuration and rock wettability on CO2 plume behaviour and CO2 trapping capacity in heterogeneous reservoirs - Al-Khdheeawi, Emad; Vialle, Stephanie; Barifcani, Ahmed; Sarmadivaleh, Mohammad; Iglauer, Stefan (Elsevier Inc., 2017)
© 2017 Elsevier B.V. CO2 geo-storage efficiency is highly affected by many factors including formation geology, storage site conditions and properties (e.g. aquifer temperature, aquifer depth, vertical to horizontal permeability ratio, cap rock properties, and reservoir heterogeneity) and the CO 2 injection process (e.g. continues injection, WAG, etc.). However, the impact of well configuration has not yet been addressed in detail. Thus, we compared the efficiency of three different vertical injection well scenarios (i.e. one well, two wells, and 4 wells) with a horizontal injection well in a deep aquifers via computer simulation; and furthermore investigated how rock wettability affects CO 2 plume migration and trapping. The results indicate that the injection well configuration has a major influence on CO 2 plume migration and on the amount of mobile, residual and dissolved CO 2 . A horizontal well reduces CO 2 plume migration, CO 2 mobility and CO 2 solubility trapping, while it improves CO 2 residual trapping. Hence, our results from a previous study, that water-wet rocks are preferable CO 2 storage formations, as they increase storage capacity and containment security, is valid for any injection well configuration. We thus conclude that from a technical perspective horizontal injection wells and from a geological perspective the more water-wet rock are preferable as they increase storage capacity and containment security.